Application of Fickian and non-Fickian diffusion models to study moisture diffusion in asphalt mastics - Apeagyei, Alex K.; Grenfell, James; Airey, Gordon (Springer, 2015)
The objective of this study was to investigate certain aspects of asphalt mastic moisture diffusion characteristics in order to better understand the moisture damage phenomenon in asphalt mixtures. Moisture sorption experiments were conducted on four asphalt mastics using an environmental chamber capable of automatically controlling both relative humidity (85 %) and temperature (23 °C). The four mastics tested were identical in terms of bitumen type (40/60 pen), bitumen amount (25 % by of wt% total mix), mineral filler amount (25 % by wt%) and fine aggregate amount (50 % by wt%). The materials differed in terms of mineral filler type (granite or limestone) and fine aggregate type (granite or limestone). Preliminary data obtained during the early part of the study showed certain anomalous behavior of the materials including geometry (thickness)-dependent diffusion coefficient. It was therefore decided to investigate some aspects related to moisture diffusion in mastics by applying the Fickian and two non-Fickian (anomalous) diffusion models to the moisture sorption data. The two non-Fickian models included a two-phase Langmuir-type model and a two-parameter time-variable model. All three models predicted moisture diffusion in mastics extremely well (R 2 > 0.95). The observed variation of diffusion coefficient with thickness was attributed in part to microstructural changes (settlement of the denser fine aggregates near the bottom of the material) during the rather long-duration diffusion testing. This assertion was supported by X-ray computed tomography imaging of the mastic that showed significant accumulation of aggregate particles near the bottom of the sample with time. The results from the Langmuir-type model support a two-phase (free and bound) model for moisture absorbed by asphalt mastic and suggests about 80 % of absorbed water in the free phase remain bound within the mastic. The results also suggest that moisture diffusion in asphalt mastic may be time-dependent with diffusion decreasing by about four times during a typical diffusion test lasting up to 500 h. The study concludes that both geometry and time-dependent physical characteristics of mastic are important factors to consider with respect to moisture diffusion in asphalt mastics.